The effects of sildenafil on heart rate variability in healthy subjects - Siepmann, Martin; Rauh, Robert; Dill, Oliver; Agelink, Marcus W.; Mück-Weymann, Michael (Journal of Cardiovascular Pharmacology, 2007)
The effects of sildenafil on heart rate variability were investigated in 20 healthy male subjects aged 24 (21 to 32) years (median; range). Subjects orally received single 100-mg doses of sildenafil and placebo under randomized double-blind crossover conditions on 2 separate study days. Time domain measures of heart rate variability were assessed under conditions of relaxed rest, metronomic breathing (6 cycles per minute), and bicycle ergometry before administration of sildenafil and placebo as well as 60 minutes afterwards. Sildenafil did not alter heart rate nor heart rate variability to a significant extent (P > 0.05). © 2007 Lippincott Williams & Wilkins, Inc.
Created from Fastlane, Scopus look-up
Keywords: Healthy subjects; Heart rate variability; Neurocardiac control; Sildenafil